The complicity of language, knowledge and justice - van Marle, Karin (Acta Academica: Critical views on society, culture and politics, 2017)
From text: In reading Pieter Duvenage’s Afrikaanse filosofie. Perspekti we en dialoë (2016) other texts came to mind – Peter Vale, Lawrence Hamilton and Estelle Prinsloo’s edited collection on Intellectual traditions in South Africa (2014); Andrew Nash’s 2000 article on what he called ‘the new politics of Afrikaans’; the majority and minority judgments in the case of City of Tshwane vs Afriforum; an article by Achille Mbembe on the decolonisation of the university, to name a few. In my reflection on Duvenage’s perspectives and dialogues I recall my thoughts arising from these texts.